Exercise performance in cold environment - Oksa, J. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
When humans are exposed to cold ambient temperatures cooling may occur and this may result in subnormal body temperatures. It is well verified that subnormal body temperature has an adverse effect on neuromuscular, cardiovascular and manual performance capacity. The amount of performance deterioration is dependent on the type and level of cooling. Neuromuscular performance In general, the ability to perform dynamic exercises is more readily disturbed by cooling than isometric exercise. Regardless of the exercise type, duration or component of performance (velocity, force etc.) decrease in dynamic performance after cooling is in the order of 2 - 10 % C-1 decrease in muscle temperature. However, during a very fast drop jump exercise the highest decrease in performance has been found to be 17 % C-1. This implies that exercise type, which is very fast and efficiently utilises the elastic properties of the working muscles is especially susceptible for cooling. A dose - response relationship between muscle temperature and performance can be found. Whether the muscle is passively cooled or actively rewarmed after cooling is of no importance; the predominant factor in determining the outcome of muscular performance is muscle temperature. In addition to decreased muscular performance cooling has also a profound effect on functional properties of skeletal muscle. For example, the rate of tension development and rate of relaxation is temperature dependent. Their temperature sensitivity (Q10) has been found to be in the order of 1.5 - 2.3. The velocity of muscle contraction itself is also slower in a given time when muscle tissue is cooled. Therefore, the power production of the muscle during shortening is less and power absorption during lengthening is more thus leading to a less powerful contraction of a muscle. Cooling also slows nerve and muscle conduction velocity, which may result in a slower and weaker muscle contraction. Cardiovascular performance Majority of the literature reports that maximal oxygen consumption and ventilation is decreased while exercising in cold and heart rate is lowered or remains unchanged. These changes can lead to decreased endurance time to exhaustion. On the other hand, at a given submaximal work load oxygen consumption and heart rate increase. Therefore, the relative metabolic strain during exercise in cold is higher. The above mentioned factors need to be taken into account while designing exercise regimes in cold. Manual performance Peripheral cooling, which usually takes place first when exposed to cold, induces decreased manual performance. The finger and hand skin temperatures between 12 - 16 C may be considered as a critical turning point after which manual performance capacity decreases abruptly.